Solve by elimination:
-2x+2y+3z=0
-2x-y+X=-3
2x+3y+3z=5
3 answers
-2x-y+X=-3 Huh ?
Oh whoops I meant
-2x-y+z=-3
-2x-y+z=-3
clearly go for the x's
add 1st and 3rd: 5y + 6z = 5
add 2nd and 3rd : 2y + 4z = 2 or y + 2z = 1
multiply that last one by 5
5y + 10z = 5 , and the other one , as is
5y + 6z = 5
subtract them:
4z = 0
z = 0
sub into y + 2z = 1
y + 0 = 1
y = 1
finally back in -2x+2y+3z=0
-2x + 2 + 0 = 0
-2x = -2
x = 1
add 1st and 3rd: 5y + 6z = 5
add 2nd and 3rd : 2y + 4z = 2 or y + 2z = 1
multiply that last one by 5
5y + 10z = 5 , and the other one , as is
5y + 6z = 5
subtract them:
4z = 0
z = 0
sub into y + 2z = 1
y + 0 = 1
y = 1
finally back in -2x+2y+3z=0
-2x + 2 + 0 = 0
-2x = -2
x = 1